Implementation of Mozart Classical Music Therapy for Pain in Post-Op Tibia Fracture Patients "Literature Review" - Zainuddin, Ricky; Wahyuni, Sunita Sri; Nihe, Rahmat B.; Kaune, Veronika (Journal La Medihealtico, 2023)
Tibial fracture is a condition where the continuity of the bone is broken due to direct or indirect trauma. Tibial fractures are one of the most common types of lower extremity fractures throughout the world. Therefore, appropriate management strategies are needed to reduce the incidence of tibia fractures and the impacts they can cause. To determine the effect of implementing Mozart classical music therapy on pain in post-op patients with tibia fractures. Descriptive analytical literature review design. Data was obtained through article search results using two electronic databases, namely Google Scholar and Garuda Portal, 167 articles were identified with a total sample size of 79 respondents. Analysis uses a map of extracted data in a grid synthesis table including author, year of publication, country, aim, sample, design, duration, results and research conclusions. This research shows that Mozart classical music therapy has been proven to have a significant effect on reducing pain in post-op patients with tibia fractures. Based on this literature review, it can be concluded that Mozart classical music therapy has proven effective in reducing pain in post-op patients with tibia fractures.